Interplay between 1,3-butadien-1,4-diyl and 2-buten-1,4-dicarbene derivatives: the quest for nucleophilic carbenes - Haberhauer, Gebhard; Gleiter, Rolf (Journal of the American Chemical Society, 2013)
By means of high level quantum chemical calculations, the influence of electron-donating heteroatomic groups (O, NH) was investigated on the 1,6-transannular ring closure of 1,6-cyclodecadiyne (8a). In the case of 8a, the bicyclo[4.4.0]deca-1,6-dien-2,7-diyl biradical 12 is generated. It was found that oxygen centers or NH groups next to the triple bond reduce the activation energy of the ring closure considerably. For the intermediate, a 2-buten-1,4-dicarbene derivative is predicted. The extension of the model calculations to two hydroxyl- or aminoacetylenes predicts the formation of the corresponding 1,3-butadien-1,4-diyl intermediates or the 2-buten-1,4-dicarbene derivatives, a member of the nucleophilic carbene family. Moreover, the calculations predict that two separated dimethoxyacetylenes are more than 7 kcal/mol less stable than the corresponding biradical and dicarbene, respectively. Possible reactions of the dicarbenes with transition metal compounds are discussed.
Gesehen am 11.02.2021